“And Brewsters pay for smiles”: Ray Bagley’s Alienated Verse - Lyon, George (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2000)
The verse of Ray Bagley, a progenitor of later «cowboy poets» in Alberta, reflects the industrial roots and character of the province, which was itself a product of the 20th century. «Cowboy culture» in Alberta is inextricably intertwined with the entertainment industry, particularly due to the presence of the Calgary Stampede, but in Bagley’s case to his connection to tourism in the Canadian Rockies. This article considers the attitudes towards history, nature, and gender expressed in Bagley’s collection of poems, Those Other Days.